Hybrid sol-gel coatings: smart and green materials for corrosion mitigation - Figueira, Rita Maria Burguete Bacelar Marreiros (2016)
Corrosion degradation of materials and metallic structures is one of the major issues that give rise to depreciation of assets, causing great financial outlays in their recovery and or prevention. Therefore, the development of active corrosion protection systems for metallic substrates is an issue of prime importance. The promising properties and wide application range of hybrid sol-gel-derived polymers have attracted significant attention over recent decades. The combination of organic polymers and inorganic materials in a single phase provides exceptional possibilities to tailor electrical, optical, anticorrosive, and mechanical properties for diverse applications. This unlimited design concept has led to the development of hybrid coatings for several applications, such as transparent plastics, glasses, and metals to prevent these substrates from permeation, mechanical abrasion, and corrosion, or even for decorative functions. Nevertheless, the development of new hybrid products requires a basic understanding of the fundamental chemistry, as well as of the parameters that influence the processing techniques, which will briefly be discussed. Additionally, this review will also summarize and discuss the most promising sol-gel coatings for corrosion protection of steel, aluminium, and their alloys conducted at an academic level.